Patterns of thyroid disorders among patients attending an endocrine clinic in Dhaka city - Hasan, Md Rakibul; Siddika, Raisa; Mou, Sayma Akther; Morshed, Md Shahed; Fakhrul Alam, Mohammad (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Data on the presentation patterns of thyroid disorders are almost lacking in Bangladesh. We present here the data of an Endocrine Outpatient Clinic based in Dhaka city. Methods: We reviewed data from the electronic health records of an Endocrine Outpatient Clinic in Dhaka, Bangladesh, over a two-year period. Thyroid function status was interpreted according to the reference range of the corresponding laboratory and classified according to the International Classification of Diseases 11th Revision (ICD-11). Results: Among 3140 patients, 1015 (32.3%) had thyroid disorders. The age of patients with thyroid disorders ranged from 1 to 84 years, with a median age of 36.0 years (interquartile range: 28.0–48.0 years), and 802 (79.0%) were female. Hypothyroidism [overt hypothyroidism, n=568 (56.0%) and subclinical hypothyroidism, n=281 (27.7%)] was the most common thyroid disorder, followed by thyrotoxicosis (106; 10.4%). Graves’ disease (n=68; 6.7%) was the most common cause of thyrotoxicosis, followed by toxic multinodular goitre (n=12; 1.2%). Structural abnormalities with euthyroid status were present in 42 (4.1%) patients. Those with overt hypothyroidism had a higher age (38.0 vs. 34.0 years; P <0.001). Diabetes and hypertension were co-existent. Participants with nodular goitre had a higher mean age (47.1 vs. 37.9 years; P =0.14 ). Conclusion: Thyroid disorders account for one-third of patients who attended an Endocrine Outpatient Clinic, with the predominance of overt hypothyroidism, followed by subclinical hypothyroidism, and thyrotoxicosis.